SINERGITAS KEBIJAKAN LEMBAGA ADAT PETANI DALAM PENANGGULANGAN KEMISKINAN DI KABUPATEN ACEH BARAT - Mardhiah, Nellis; Syahputri, Veni Nella; Nodi Marefanda, Nodi Marefanda; Macella, Agatha Debby Reiza (Universitas Riau Kepulauan, 2024)
Abstract: The aim of this research is to understand the synergy pattern implementation of government policies in accordance with the qanun of traditional farmer institutions number 10 of 2008 in article 25 discusses about traditional farmer institutions have duties and functions that can be synergized by the government village. The rice farming community is always on the poverty line, the dynamics of the socio-economic layers of the farming community are still very attached to values and culture which are often ignored by the government and traditional institutions with unidirectional organizational communication patterns, there are conflicts of interest in increasing the productivity of rice agricultural products. The SDGs-18 Development Target for farming communities is an element of strengthening dynamic village institutions and an adaptive culture which is one of the development prospects in changing the direction of social policy and community empowerment for village development in overcoming poverty. The traditional institution